2012
DOI: 10.1002/nbm.2817
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo ultrahigh field 14.1 T 1H‐MRS study on 6‐OHDA and α‐synuclein‐based rat models of Parkinson's disease: GABA as an early disease marker

Abstract: The detection of Parkinson's disease (PD) in its preclinical stages prior to outright neurodegeneration is essential to the development of neuroprotective therapies and could reduce the number of misdiagnosed patients. However, early diagnosis is currently hampered by lack of reliable biomarkers. 1 H magnetic resonance spectroscopy (MRS) offers a noninvasive measure of brain metabolite levels that allows the identification of such potential biomarkers. This study aimed at using MRS on an ultrahigh field 14.1 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…) or increase in GABA but a decrease in Glu (Coune et al . ). Increased GABA in striatum has also been reported in patients with mild PD (Emir et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…) or increase in GABA but a decrease in Glu (Coune et al . ). Increased GABA in striatum has also been reported in patients with mild PD (Emir et al .…”
Section: Discussionmentioning
confidence: 97%
“…) and in a model of early PD based on adeno‐associated virus (AAV)‐mediated expression of human α‐synuclein (Coune et al . ), suggesting that striatal GABA levels are a sensitive marker of parkinsonism. The lack of significant changes in possible indicators of energy metabolism defect (Cr) or cell viability (NAA) in BG components is consistent with the absence of evidence for neurodegeneration within the striatum and SNr in acute animal models of PD and agrees with previous reports (Chassain et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This current 1 H MR spectroscopic study did not observe changes in Glx pool, which converges with previous studies in PD patients (15,32) but diverges from data obtained in animal models. Indeed, MR spectroscopic studies in animal models of PD suggest that dopaminergic denervation induces hyperactivity of the glutamatergic corticostriatal pathway, where the elevated glutamate concentrations observed inside the striatum were associated with increased glutamine and g-aminobutyric acid levels, which points to modified neuron-glia interactions inside this structure after dopaminergic denervation (18,20,33). As the modifications observed are associated with an acute lesion of the nigrostriatal pathway, changes in glutamate and glutamine in animal studies might reflect a temporary glial response in the striatum in response to dopaminergic denervation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Although GABAergic neurons are not typically associated with signs or symptoms of major neurodegenerative or neurodevelopmental diseases, recent research has demonstrated their importance in the early symptomology of Parkinson’s disease [8,17,35] and Alzheimer’s disease [39,47,54]. In our herbicide model, however, these GABAergic ventral nerve cord neurons do not appear to contribute significantly (Figure 3) to the loss of green pixels observed in the pan-neuronal::GFP studies (Figure 2).…”
Section: Discussionmentioning
confidence: 99%